Writing/erasing 3D micro and nano wrinkles in flexible elastomers for volatile organic compounds sensor - Fernandes, Joana Gonçalves (2014)
Micro/nano wrinkled patterns on cross-linked urethane/urea polymeric flexible free standing films with two soft segments, polypropylene oxide and polybutadiene, can be induced by UV-irradiation. The ability to write/erase these 3D structures, in a controlled manner, is the main focus of this work. The imprinting of the wrinkled structures was accomplished by swelling in an appropriate solvent followed by drying the membranes after the cross-linking process and UV irradiation. The surface tailoring of the elastomeric membranes was imaged by optical microscopy, scanning electronic microscopy and by atomic force microscopy. To erase the wrinkled structures the elastomers were swollen. The swelling as well as the sol/gel fraction and the UV radiation were tuned in order to control the wrinkles characteristics. It was found that the wrinkles wavelength, in the order of microns (1±0,25μm), was stamped by the UV radiation intensity and exposure time while the wrinkles' amplitude, in the order of nanometers (150-450 nm), was highly dependent on the swelling and sol/gel fraction. A prototype for volatile organic compounds detection was developed taking advantage of the unique 3D micro/nano wrinkles features.